An integrative analysis of the lncRNA-miRNA-mRNA competitive endogenous RNA network reveals potential mechanisms in the murine hair follicle cycle - Ding, Yuxin; Chen, Yuhong; Yang, Xiaoshuang; Xu, Piaopiao; Jing, Jing; Miao, Yujie; Mao, Meiqi; Xu, Jiali; Wu, Xianjie; Lu, Zhongfa (Frontiers in Genetics, 2022)
Alopecia is a common progressive disorder associated with abnormalities of the hair follicle cycle. Hair follicles undergo cyclic phases of hair growth (anagen), regression (catagen), and rest (telogen), which are precisely regulated by various mechanisms. However, the specific mechanism associated with hair follicle cycling, which includes noncoding RNAs and regulation of competitive endogenous RNA (ceRNA) network, is still unclear. We obtained data from publicly available databases and performed real-time quantitative polymerase chain reaction validations. These analyses revealed an increase in the expression of miRNAs and a decrease in the expression of target mRNAs and lncRNAs from the anagen to telogen phase of the murine hair follicle cycle. Subsequently, we constructed the ceRNA networks and investigated their functions using enrichment analysis. Furthermore, the androgenetic alopecia (AGA) microarray data analysis revealed that several novel alopecia-related genes were identified in the ceRNA networks. Lastly, GSPT1 expression was detected using immunohistochemistry. Our analysis revealed 11 miRNAs (miR-148a-3p, miR-146a-5p, miR-200a-3p, miR-30e-5p, miR-30a-5p, miR-27a-3p, miR-143-3p, miR-27b-3p, miR-126a-3p, miR-378a-3p, and miR-22-3p), 9 target mRNAs (Atp6v1a, Cdkn1a, Gadd45a, Gspt1, Mafb, Mitf, Notch1, Plk2, and Slc7a5), and 2 target lncRNAs (Neat1 and Tug1) were differentially expressed in hair follicle cycling. The ceRNA networks were made of 12 interactive miRNA-mRNA pairs and 13 miRNA-lncRNA pairs. The functional enrichment analysis revealed the enrichment of hair growth–related signaling pathways. Additionally, GSPT1 was downregulated in androgenetic alopecia patients, possibly associated with alopecia progression. The ceRNA network identified by our analysis could be involved in regulating the hair follicle cycle.